Design of a test rig for in situ hydrogen charging of rolling element bearings under load - Moström, Oskar (Luleå tekniska universitet, Maskinelement, 2023)
This Master's thesis is part of the Hydrogen Embrittlement in Rolling element bearings project (HERo) initiated at Luleå University of Technology (LTU), with the primary objective of determining critical hydrogen concentrations in bearing steel for rolling element bearings. The specific aim of this Master's thesis is to design a test rig that enables the investigation of the effects of hydrogen embrittlement on rolling element bearings under load. The design process focused on ease of manufacture and assembly. The developed test rig includes an electric motor, a pneumatic load application mechanism, and an electrochemical cell. Using the leverage principle, a thrust roller bearing is loaded vertically, while it is driven by an electric motor that is connected to the bearing with a tyre coupling. The electrochemical cell, which consists of a reference electrode, counter electrode, and the test bearing as the working electrode, is used to charge the test bearing with hydrogen. The cell was designed to be easily accessible between tests to facilitate the change of thrust roller bearings. The test bench enables the analysis of rolling element bearings that are exposed to simultaneous hydrogen embrittlement and realistic operating conditions. Detta examensarbete är en del av Hydrogen Embrittlement in Rolling element bearings-projektet (HERo) som pågår vid Luleå tekniska universitet (LTU), med huvudmålet att bestämma de kritiska vätekoncentrationerna i lagerstål för rullningslager. Det specifika målet med detta examensarbete är att konstruera en testrigg för att direkt undersöka effekten av väteförsprödning av lager i en simulerad verklig tillämpning. Designprocessen fokuserade på enkel tillverkning och montering. Den utvecklade testriggen inkluderar en elmotor, en pneumatisk lastpåläggnings-mekanism och en elektrokemisk cell. Med hjälp av hävstångsprincipen belastas ett axiellt rullager vertikalt, medan det drivs av en elmotor via en däckkoppling. Den elektrokemiska cellen, som består av en referenselektrod, ...